Non-destructive Evaluation of Corrosion in Reinforced Concrete using Field Spectroscopy and Remote Sensing - Christofe, Andreas (My University, 2023)
This PhD Thesis aims to study the reinforced concrete (RC) properties using remote sensing techniques and propose a novel remote sensing method for the inspection and non-destructive evaluation of corrosion in concrete structures. This new corrosion detection method on concrete structures could be incorporated into any existing Structural Health Monitoring (SMH) system to accelerate and simplify the inspection process and reduce monitoring costs. For this purpose, a three-stage novel methodology is proposed. The first stage concerns the study of concrete spectral characteristics (spectral signatures) due to the control exposure in an aggressive sodium chloride environment using a salt spray chamber and a spectroradiometer. The second stage explores and determines the spectral regions suitable for the identification of corrosion products found on concrete surfaces, and the development of a dedicated Rust Index. Finally, the third stage focuses on the incorporation of a Rust Index into the existing SMH systems through the available market solutions. The results showed that there was a uniform increase in the reflectance response after the curing period of the concrete specimens (from 28 days until 90 days) in the wavelength range studied (400 – 2500 nm), while a uniform decrease was evident compared the period of the sodium chloride exposure duration (aging), for the three concrete categories examined. Furthermore, a significant variation in the reflectance response was noted in the spectral region 650nm to 900nm between the surface area having corrosion products (Rust) and a surface area without corrosion products (No Rust) and a novel dedicated Rust Index was created using simple arithmetic operations. Finally, the Rust Index was modified and integrated into available market solutions (drone multispectral camera). The mapping of corrosion products on the concrete surface was visualised through ArcGIS PRO software after the in-situ specimens inspection test.
Keywords: Concrete; Concrete Structures; Corrosion in Concrete; Concrete Aging Remote Sensing; Spectroradiometer; ArcGIS PRO; Structural Health Monitoring